Perovskite composite disulfide thin film material and preparation method and application thereof

By doping perovskite materials into dichalcogen compound films to form ABX3-MY2 composite films, the problem of insufficient friction performance of transition metal dichalcogen compound films in the field of space and aerospace in the prior art is solved, and low friction is achieved and long-lived lubrication effect.

CN119433440APending Publication Date: 2025-02-14LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411913426.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing transition metal dichalcogen films are difficult to meet the requirements of low friction and long life in the space aerospace field.

Method used

By doping perovskite material into the dichalcogen compound film, the ABX3-MY2 composite film was formed, and the composite film was prepared by radiofrequency sputtering technology.

Benefits of technology

It effectively improves the crystallinity, crystal orientation, microstructure and surface morphology of the film, significantly reduces the friction coefficient and extends the friction life, making it have application prospects in the field of spatial lubrication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433440A_ABST
    Figure CN119433440A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite composite disulfide thin film material as well as a preparation method and application thereof. The perovskite composite disulfide thin film material is an ABX3-MY2 composite thin film, wherein A is one or more + 1 valence or + 2 valence metal or organic cations; b is one or more + 2 or + 4 metal or organic cations; x is one or more of-1-valent or-2-valent nonmetal or organic anions; m is a IV-VI group transition metal, and Y is a chalcogenide element. The perovskite material is doped in the layered transition metal disulfide compound material, so that the crystallinity, the crystal orientation, the microstructure and the surface appearance of the disulfide compound in the film can be effectively improved, the tribological performance of the film in a vacuum environment is further improved, and the film has a certain application prospect in the field of space lubrication.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a perovskite composite disulfide compound thin film material and a preparation method and application thereof. Background Art

[0002] Transition metal dichalcogenides (TMDs), such as molybdenum disulfide (MoS2) and tungsten disulfide (WS2), have a wide range of applications in solid lubrication, energy catalysis, optoelectronic devices, and biosensors due to their typical two-dimensional structure, excellent stability, and unique electronic structure. By regulating the crystal orientation, stacking mode, and organizational morphology of such materials, the physical and chemical properties of such materials can be effectively improved, thereby enhancing their performance in related application fields.

[0003] In order to further improve the lubrication performance of transition metal dichalcogenides (TMDs), many researchers have conducted extensive research on RF sputtering of MoS2 or WS2 films. However, it still fails to meet the requirements of future space aerospace for low friction and long life of solid lubricating films. Therefore, it is necessary to controllably construct the organization and structure of transition metal dichalcogenide film materials to improve their tribological properties. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a perovskite composite disulfide compound thin film material. The perovskite composite disulfide compound thin film material can have a low friction coefficient and a long friction life in a space environment.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned perovskite composite disulfide compound thin film material.

[0006] The present invention also provides application of the above-mentioned perovskite composite disulfide compound thin film material.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] A perovskite composite disulfide compound thin film material, wherein the perovskite composite disulfide compound thin film material is an ABX3-MY2 composite film; wherein A is one or more +1-valent or +2-valent metals or organic cations; B is one or more +2-valent or +4-valent metals or organic cations; X is one or more -1-valent or -2-valent non-metals or organic anions; M is a transition metal of Group IV to VI, and Y is a chalcogen element; wherein the perovskite and the disulfide compound exist in a nanocrystalline or amorphous structure to form a composite film together.

[0009] The present invention dopes the disulfide compound (MY2) material with the perovskite (ABX3) material, which can effectively improve the crystallinity, crystal orientation, microstructure and surface morphology of the disulfide compound in the film, and effectively improve the tribological properties of the film in a vacuum environment. According to measurements, the friction coefficient of the perovskite composite disulfide compound film material of the present invention ranges from 0.009 to 0.020; the friction life ranges from 1.0×10 5 ~ 1.0×10 6 lock up.

[0010] Preferably, A is Ca 2+ , Ba 2+ , Sr 2+ , Cs + NHCHNH2 + (FA + )、CH3NH2 + (MA + ), NH4 + One or more of; B is Ti 4+ , Mn 4+ , Pb 2+ Sn 2 + ,MDABCO 2+ One or more of; X is O 2- , Cl - ,Br - ,I - One or more of the following;

[0011] M is Mo or W, and Y is S or Se.

[0012] Preferably, the thickness of the perovskite composite dichalcogenide thin film material is 0.3-5.0 μm; more preferably, the thickness is 1-3 μm.

[0013] Preferably, the perovskite composite dichalcogenide compound thin film material is an ABX3-WS2 thin film, and the thickness of the ABX3-WS2 thin film is 0.8-2 μm;

[0014] Or the perovskite composite disulfide compound thin film material is an ABX3-MoS2 thin film, the ABX3-MoS2 thin film has a thickness of 2-3 μm and an average grain size of 170-600 nm.

[0015] More preferably, the perovskite composite disulfide compound film material is a BaTiO3-WS2 film, the structure of the BaTiO3-WS2 film is a vertically grown flaky crystal, and the average size of the flaky crystal is 360 nm;

[0016] Or, the perovskite composite disulfide compound film material is a SrTiO3-WS2 film, the structure of the SrTiO3-WS2 film is short columnar crystals growing vertically, the surface of the short columnar crystals is granular, and the average size of the granular crystals is 24 nm;

[0017] Alternatively, the perovskite composite disulfide compound thin film material is a BaSrTiO3-WS2 thin film, and the structure of the BaSrTiO3-WS2 thin film is stacked and grown nanoparticles, and the average size of these nanoparticles is 16 nm.

[0018] Preferably, the perovskite composite dichalcogenide thin film material is ABX3-MY2, wherein the mass ratio of ABX3 to MY2 is (1-20):100.

[0019] The preparation method of the above-mentioned perovskite composite disulfide compound thin film material, wherein the preparation raw materials include perovskite (ABX3) and layered transition metal disulfide compound (MY2);

[0020] The perovskite is a material with an ABX3 structure, wherein A is one or more +1-valent or +2-valent metals or organic cations; B is one or more +2-valent or +4-valent metals or organic cations; and X is one or more -1-valent or -2-valent non-metals or organic anions.

[0021] The layered transition metal dichalcogenides (TMDs) are materials with a MY2 structure, wherein M is a transition metal of Group IV to VI, and Y is a chalcogen element.

[0022] Preferably, the perovskite material is CaTiO3, BaTiO3, SrTiO3, Ba 0.5 Sr 0.5 TiO3, CsPbBr3, MAFAPbI3, MAPbClBr2, MAPbSnI3, MDABCO-NH4I3, etc.

[0023] Preferred layered transition metal dichalcogenides are MoS2, WS2, etc.

[0024] The preparation method is specifically to sputter a composite target of perovskite and transition metal disulfide compound onto a substrate surface by radio frequency sputtering to obtain the perovskite composite disulfide compound lubricating film material. The mass ratio of perovskite to transition metal disulfide compound in the composite target can be any ratio, and preferably the mass of transition metal disulfide compound is greater than the mass of perovskite.

[0025] Alternatively, the preparation method is specifically to simultaneously sputter a perovskite target material and a layered transition metal disulfide target material on the surface of a substrate by a radio frequency co-sputtering method to obtain the perovskite composite disulfide compound lubricating film material.

[0026] Preferably, the sputtering gas pressure ranges from 1 to 10 Pa;

[0027] Preferably, the sputtering bias ranges from -10 to -60 V;

[0028] Preferably, the argon gas flow rate ranges from 10 to 60 sccm;

[0029] Preferably, the sputtering power ranges from 100 to 300 W;

[0030] Preferably, the substrate temperature ranges from 25 to 400 °C

[0031] Preferably, the turntable speed ranges from 1 to 10 rpm.

[0032] The present invention also provides the application of the perovskite composite disulfide compound film material described in the above technical solution in the field of solid lubrication.

[0033] The beneficial effects of the present invention are as follows:

[0034] (1) The present invention dopes perovskite materials into layered transition metal disulfide materials, which can effectively improve the crystallinity, crystal orientation, microstructure and surface morphology of disulfide compounds in the film, and effectively enhance the tribological properties of the film in a vacuum environment, making it have certain application prospects in the field of space lubrication.

[0035] (2) Perovskite doping can enhance the crystallinity of layered transition metal dichalcogenides, effectively reduce the friction coefficient of layered transition metal dichalcogenide films, and improve their tribological properties.

[0036] (3) Perovskite doping can effectively inhibit the oxidation of layered transition metal dichalcogenides, effectively prolong the friction life of layered transition metal dichalcogenide films, and improve their tribological properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a diagram of the elemental composition of the perovskite composite tungsten disulfide thin films prepared in Examples 1 to 3.

[0038] Figure 2 Cross-sectional and surface SEM images of the perovskite composite tungsten disulfide thin films prepared in Examples 1 to 3 on a silicon wafer substrate.

[0039] Figure 3Surface Raman spectra of the perovskite composite tungsten disulfide thin films prepared in Examples 1 to 3 and the pure tungsten disulfide thin film prepared in Comparative Example 1.

[0040] Figure 4 XRD patterns of the perovskite composite tungsten disulfide thin films prepared in Examples 1 to 3 and the pure tungsten disulfide thin film prepared in Comparative Example 1.

[0041] Figure 5 Friction curves of the perovskite composite tungsten disulfide films prepared in Examples 1 to 3 and the pure tungsten disulfide film prepared in Comparative Example 1.

[0042] Figure 6 The element compositions of the perovskite composite molybdenum disulfide films prepared in Examples 4 to 6.

[0043] Figure 7 Cross-sectional and surface SEM images of the perovskite composite molybdenum disulfide thin films prepared in Examples 4 to 6 on a silicon wafer substrate.

[0044] Figure 8 Surface Raman spectra of the perovskite composite molybdenum disulfide thin films prepared in Examples 4 to 6 and the pure molybdenum disulfide thin film prepared in Comparative Example 2.

[0045] Fig. 9 XRD patterns of the perovskite composite molybdenum disulfide thin films prepared in Examples 4 to 6 and the pure molybdenum disulfide thin film prepared in Comparative Example 2.

[0046] Fig.10 Friction curves of the perovskite composite molybdenum disulfide films prepared in Examples 4 to 6 and the pure molybdenum disulfide film prepared in Comparative Example 2.

[0047] Fig.11 The Ba prepared in Example 6 0.5 Sr 0.5 Transmission electron microscopy (TEM) images of TiO3-MoS2 thin films on AISI 400C substrate.

[0048] Fig.12 The Ba prepared in Example 6 0.5 Sr 0.5 Energy dispersive spectrometer elemental analysis (EDS) image of TiO3-MoS2 thin film on AISI 400C substrate.

[0049] Fig.13 The Ba prepared in Example 6 0.5 Sr 0.5 High-resolution TEM image of TiO3-MoS2 thin film on AISI 400C substrate.

[0050] Fig.14This is the friction curve of the CaTiO3-WS2 film prepared in Example 7. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0052] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0053] The present invention does not have any special limitation on the application method, and the application method may be carried out by methods well known to those skilled in the art.

[0054] The perovskite composite disulfide compound thin film material provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0055] Example 1

[0056] The substrate (AISI 400C steel block or silicon wafer) was ultrasonically cleaned with petroleum ether, ethanol and acetone for 20 min in sequence, and then dried for use. The perovskite BaTiO3 target with a purity of 99.0% and the transition metal dichalcogenide WS2 target with a purity of 99.9% were fixed on the two RF guns of the RF sputtering instrument, and the cleaned substrate was placed on the turntable in the sputtering chamber, and the hatch was closed; the air pressure in the sputtering chamber was pumped down to 1.0×10 -3 Pa, argon gas with a purity of 99.9% is introduced, the flow rate of the argon gas is 30 sccm, the gas pressure in the sputtering chamber is 8.0 Pa, the bias voltage is -500 V, and the surface of the substrate is cleaned with Ar ions for 30 min; after cleaning, the gas pressure in the sputtering chamber is pumped to 5 Pa, the bias voltage is -30 V, the baffle is opened, the sample turntable is started, the speed is 2 rpm, the sputtering power of the WS2 target is adjusted to 200 W, the sputtering power of the BaTiO3 target is adjusted to 140 W, the sputtering time is 30 min, and a BaTiO3-WS2 thin film is obtained.

[0057] Example 2

[0058] The specific preparation process refers to Example 1, except that the sputtering gas pressure is 3 Pa; the sputtering bias is -10 V; the argon gas flow rate is 60 sccm; the substrate temperature is 25 °C, the turntable speed is 2 rpm, the perovskite target is SrTiO3, the sputtering power of the SrTiO3 target is 200 W, and the sputtering power of the WS2 target is 200 W, to obtain a SrTiO3-WS2 film.

[0059] Example 3

[0060] The specific preparation process is as in Example 1, except that the sputtering pressure is 1 Pa; the sputtering bias is -40 V; the argon flow rate is 20 sccm; the substrate temperature is 400 °C, the turntable speed is 4 rpm, and the perovskite target is Ba 0.5 Sr 0.5 TiO3, the composite target is formed by mixing and sintering BaTiO3 and SrTiO3 in equal molar ratios, and is abbreviated as BaSrTiO3 in the figure for simplicity of expression. The sputtering power of the BaSrTiO3 target is 160 W, and the sputtering power of the WS2 target is 200 W, to obtain a BaSrTiO3-WS2 thin film.

[0061] Comparative Example 1

[0062] Refer to Example 1, except that the sputtering power of the BaTiO3 target is 0 W, the sputtering power of the WS2 target is 200 W, the sputtering time is 30 min, the substrate temperature is 200 °C, the turntable speed is 2 rpm, and a WS2 thin film is obtained.

[0063] Figure 1 The element composition of the perovskite composite tungsten disulfide film prepared in Examples 1 to 3 is Figure 1 From the proportion of elements in the film, it can be seen that the atomic percentage of BaTiO3 in the BaTiO3-WS2 film of Example 1 is about 13.8%, of which Ba accounts for 2.6%, Ti accounts for 2.9%, and O accounts for 8.3% (calculated based on the BaTiO3 structure); the atomic percentage of SrTiO3 in the SrTiO3- WS2 film of Example 2 is about 18.8%, of which Sr accounts for 3.6%, Ti accounts for 3.9%, and O accounts for 11.3% (calculated based on the SrTiO3 structure); the atomic percentage of BaSrTiO3 in the BaSrTiO3- WS2 film of Example 3 is about 15.9%, of which Ba accounts for 1.5%, Sr accounts for 1.6%, Ti accounts for 3.2%, and O accounts for 9.6% (calculated based on the Ba 0.5 Sr 0.5The ratio of each element in the film shows that the composition of each element in the sputtered film is basically consistent with that in the target material, indicating that the RF co-sputtering method can effectively incorporate perovskite into the WS2 film.

[0064] Figure 2 The cross-sectional and surface SEM images of the perovskite composite tungsten disulfide films prepared in Examples 1 to 3. It can be seen that the structures of different types of perovskite composite tungsten disulfide films are quite different, wherein the BaTiO3-WS2 film of Example 1 has a thickness of 1.71 μm, a structure of vertically grown flaky crystals, a petal-shaped surface, and an average size of flaky crystals of 360 nm; the SrTiO3- WS2 film of Example 2 has a thickness of 0.95 μm, a structure of vertically grown short columnar crystals, a granular surface, and an average size of granular crystals of 24 nm; the BaSrTiO3- WS2 film of Example 3 has a thickness of 0.96 μm, a structure of stacked-grown nanoparticles, and an average size of these nanoparticles of 16 nm.

[0065] Figure 3 The surface Raman spectra of the perovskite composite tungsten disulfide films prepared in Examples 1 to 3 and the pure tungsten disulfide film prepared in Comparative Example 1. It can be seen that the Raman spectra of all films at 352 cm -1 and 418 cm -1 The two strong Raman peaks at 1 2g and outer surface A 1g The vibration peaks indicate that there is an ordered WS2 structure in all films; and the characteristic peak signal of WS2 in the perovskite composite tungsten disulfide film is stronger, indicating that perovskite doping can effectively enhance the crystallinity. At the same time, perovskite can effectively inhibit the oxidation of WS2 in the air.

[0066] Figure 4 The XRD patterns of the perovskite composite tungsten disulfide films prepared in Examples 1 to 3 and the pure tungsten disulfide film prepared in Comparative Example 1 are shown. It can be seen that the (101) crystal plane of the BaTiO3-WS2 film in Example 1 is higher than that of the pure WS2 film, indicating that BaTiO3 doping can effectively improve the crystallinity of WS2; the (101) crystal plane of the SrTiO3-WS2 film in Example 2 is significantly lower than that of the pure WS2 film, and the (001) crystal plane appears, indicating that SrTiO3 doping can effectively improve the crystal orientation of WS2; and the (101) crystal plane in the BaSrTiO3-WS2 film in Example 3 disappears, and only the strong (001) crystal plane is present, indicating that BaSrTiO3 can not only improve the crystallinity of WS2, but also improve the crystal orientation of the film.

[0067] Figure 5 The friction curves of the perovskite composite tungsten disulfide film prepared in Examples 1 to 3 and the pure tungsten disulfide film prepared in Comparative Example 1 are shown in Figure 1. The average friction coefficient of the pure WS2 film is 0.039, and the friction life is 1.36×10 5 The average friction coefficient of the BaTiO3-WS2 film of Example 1 is 0.016, and the friction life is 3.85×10 5 The average friction coefficient of the SrTiO3-WS2 film of Example 2 is 0.019, and the friction life is 3.34×10 5 The average friction coefficient of the BaSrTiO3-WS2 film of Example 3 is 0.012, and the friction life is 6.15×10 5 The above results show that perovskite doping can effectively reduce the friction coefficient of WS2 film and improve the tribological properties.

[0068] Example 4

[0069] Refer to Example 1, except that the sputtering gas pressure is 10 Pa; the sputtering bias is -60 V; the argon gas flow rate is 40 sccm; the substrate temperature is 200 °C, and the turntable speed is 4 rpm; the perovskite target is BaTiO3, the transition metal dichalcogenide target is MoS2, the sputtering power of the SrTiO3 target is 140 W, and the sputtering power of the MoS2 target is 200 W, and a BaTiO3-MoS2 thin film is obtained.

[0070] Example 5

[0071] Refer to Example 1, except that the sputtering gas pressure is 5 Pa; the sputtering bias is -30 V; the argon gas flow rate is 30 sccm; the substrate temperature is 400 °C, the turntable speed is 4 rpm, the perovskite target is SrTiO3, the transition metal dichalcogenide target is MoS2, the sputtering power of the SrTiO3 target is 140 W, and the sputtering power of the WS2 target is 200 W, and a SrTiO3-MoS2 thin film is obtained.

[0072] Example 6

[0073] Refer to Example 1, except that the sputtering gas pressure is 7 Pa; the sputtering bias is -40 V; the argon flow rate is 30 sccm; the substrate temperature is 100 °C, the turntable speed is 4 rpm, the perovskite target is BaSrTiO3, the transition metal dichalcogenide target is MoS2, the sputtering power of the BaSrTiO3 target is 140 W, and the sputtering power of the WS2 target is 200 W, and a BaSrTiO3-MoS2 thin film is obtained.

[0074] Comparative Example 2

[0075] Refer to Example 1, except that the sputtering gas pressure is 7 Pa; the sputtering bias is -40 V; the argon gas flow rate is 30 sccm; the substrate temperature is 100 °C, the turntable speed is 4 rpm, the sputtering power of the BaTiO3 target is 0 W, the transition metal dichalcogenide target is MoS2, and the sputtering power of the MoS2 target is 200 W, to obtain a MoS2 thin film.

[0076] Test Method

[0077] The tribological properties of the perovskite composite disulfide compound films described in Examples 1 to 6 and the WS2 and MoS2 films described in Comparative Examples 1 to 2 in a vacuum environment were evaluated using a vacuum ball-disc friction tester, wherein the dual friction pair was an AISI 400C steel ball with a diameter of 8 mm;

[0078] The test conditions of vacuum tribological performance were as follows: normal load 5 N, rotation radius 5 mm, rotation speed 1000 rpm, and the background vacuum of the friction tester chamber was better than 1.0×10 -3 Pa, the friction coefficient is set to be greater than 0.15 as lubrication failure, and the test temperature is room temperature.

[0079] Figure 6 The element composition of the perovskite composite molybdenum disulfide film prepared in Examples 4 to 6 is Figure 6 From the ratio of elements in the film, it can be seen that the atomic percentage of BaTiO3 in the BaTiO3-MoS2 film of Example 4 is about 12.5%, of which Ba accounts for 2.5%, Ti accounts for 2.5%, and O accounts for 7.5% (calculated based on the BaTiO3 structure); the atomic percentage of SrTiO3 in the SrTiO3-WS2 film of Example 5 is about 11.0%, of which Sr accounts for 2.1%, Ti accounts for 2.3%, and O accounts for 6.6% (calculated based on the SrTiO3 structure); the atomic percentage of BaSrTiO3 in the BaSrTiO3-WS2 film of Example 6 is about 9.6%, of which Ba accounts for 1.1%, Sr accounts for 0.9%, Ti accounts for 1.9%, and O accounts for 5.7% (calculated based on the BaSrTiO3 structure). From the ratio of each element in the film, it can be seen that the composition of each element sputtered is basically consistent with that in the target material, indicating that the RF co-sputtering method can effectively incorporate perovskite into MoS2 film.

[0080] Figure 7The cross-sectional and surface SEM images of the perovskite composite molybdenum disulfide films prepared in Examples 4 to 6. It can be seen that the thickness and structure of different types of perovskite composite molybdenum disulfide films are basically similar, wherein the thickness of the BaTiO3-MoS2 film in Example 4 is 2.42 μm, and the average grain size is 178 nm; the thickness of the SrTiO3-MoS2 film in Example 5 is 2.82 μm, and the average grain size is 277 nm; the thickness of the BaSrTiO3-MoS2 film in Example 6 is 2.80 μm, and the average grain size is 594 nm.

[0081] Figure 8 The surface Raman spectra of the perovskite composite molybdenum disulfide films prepared in Examples 4 to 6 and the pure molybdenum disulfide film prepared in Comparative Example 2. It can be seen that the Raman spectra of all films at 358 cm -1 and 403 cm -1 There are two Raman peaks at 1 2g and outer surface A 1g The vibration peaks indicate that there is an ordered MoS2 structure in all films; and the characteristic peak signal of MoS2 in the perovskite composite tungsten disulfide film is slightly enhanced, indicating that perovskite doping can slightly enhance the crystallinity of MoS2. At the same time, the 829 cm-1 peak does not appear in the perovskite composite molybdenum disulfide film. -1 The characteristic peak of Mo oxide is at the bottom, indicating that perovskite doping can effectively inhibit the oxidation of MoS2.

[0082] Fig. 9 XRD patterns of the perovskite composite molybdenum disulfide films prepared in Examples 4 to 6 and the pure molybdenum disulfide film prepared in Comparative Example 2. It can be seen that the (101) crystal plane diffraction peak intensity of the perovskite composite molybdenum disulfide film is higher than that of the pure WS2 film, and the signal of the BaSrTiO3-MoS2 film in Example 6 is the strongest, indicating that BaSrTiO3 has the best crystallization enhancement effect on molybdenum disulfide.

[0083] Fig.10 The friction curves of the perovskite composite molybdenum disulfide film prepared in Examples 4 to 6 and the pure molybdenum disulfide film prepared in Comparative Example 2 are shown in Figure 2. The average friction coefficient of the pure MoS2 film in Comparative Example 2 is 0.072, and the friction life is 0.92×10 5 The average friction coefficient of the BaTiO3-MoS2 film of Example 4 is 0.021, and the friction life is 7.21×10 5 The average friction coefficient of the SrTiO3-MoS2 film of Example 5 is 0.030, and the friction life is 2.54×10 5The average friction coefficient of the BaSrTiO3-MoS2 film of Example 6 is 0.020, and the friction life exceeds 10.0×10 5 circle; The above results show that perovskite doping can effectively reduce the friction coefficient of WS2 film and improve the tribological properties, and BaSrTiO3 perovskite has the best effect.

[0084] Fig.11 This is a transmission electron microscope (TEM) image of the BaSrTiO3-MoS2 thin film on an AISI 400C substrate prepared in Example 6. It can be seen that the film has a thickness of 1.51 μm and has an obvious dense layer and a columnar crystal layer with thicknesses of 0.65 μm and 0.86 μm, respectively.

[0085] Fig.12 This is an energy dispersive spectrometer elemental analysis (EDS) image of the BaSrTiO3-MoS2 film on an AISI 400C substrate prepared in Example 6. It can be seen that there are obvious element signals of Ba, Sr, Ti, O, Mo and S in the film, indicating that the composite film is composed of BaSrTiO3 and MoS2.

[0086] Fig.13 This is a high-resolution TEM image of the BaSrTiO3-MoS2 film on an AISI 400C substrate prepared in Example 6. It can be seen that there are a large number of MoS2 nanocrystals in the film, with a size between 5 and 10 nm.

[0087] Example 7

[0088] The substrate (AISI 400C steel block) was ultrasonically cleaned with petroleum ether, ethanol and acetone for 20 min in turn, and then dried for use. The perovskite CaTiO3 with a purity of 99.0% and the transition metal dichalcogenide WS2 with a purity of 99.9% were pressed and sintered in a mass ratio of 20:100 to form a composite target; the composite target was fixed to the radio frequency gun of the radio frequency sputtering instrument, the cleaned substrate was placed on the turntable in the sputtering chamber, and the hatch was closed; the air pressure in the sputtering chamber was pumped to 1.0×10 -3 Pa, argon gas with a purity of 99.9% was introduced, the flow rate of the argon gas was 50 sccm, the gas pressure in the sputtering chamber was 8.0 Pa, the bias voltage was -500 V, and the surface of the substrate was cleaned with Ar ions for 30 min; after cleaning, the gas pressure in the sputtering chamber was pumped to 5 Pa, the bias voltage was -30 V, the baffle was opened, the sample turntable was started, the speed was 3 rpm, the sputtering power of the composite target was adjusted to 200 W, and the sputtering time was 30 min to obtain the CaTiO3-WS2 thin film.

[0089] Fig.14The friction curve of the CaTiO3-WS2 film prepared in Example 7. The average friction coefficient of the pure MoS2 film in Example 7 is 0.017, and the friction life exceeds 6.0×10 5 The performance is also better than that of Comparative Example 1.

[0090] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0091] The parts not elaborated in detail in the description of the present invention belong to the known technology in the art. The above embodiments are provided only for the purpose of describing the present invention, and are not intended to limit the scope of the present invention. The scope of the present invention is defined by the appended claims. Various equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included in the scope of the present invention.

Claims

1. A perovskite composite dichalcogenide thin film material, characterized in that: The perovskite composite dichalcogenide thin film material is an ABX3-MY2 composite thin film; A is one or more +1-valent or +2-valent metals or organic cations; B is one or more +2-valent or +4-valent metals or organic cations; X is one or more -1-valent or -2-valent non-metals or organic anions; M is a transition metal of Group IV to VI, and Y is a chalcogen element.

2. The perovskite composite dichalcogenide compound thin film material according to claim 1, characterized in that: A is Ca 2+ , Ba 2 + , Sr 2+ , Cs + NHCHNH2 + (FA + )、CH3NH2 + (MA + ), NH4 + One or more of; B is Ti 4+ , Mn 4+ , Pb 2+ Sn 2 + ,MDABCO 2+ One or more of; X is O 2- , Cl - ,Br - ,I - One or more of the following; M is Mo or W, and Y is S or Se.

3. The perovskite composite dichalcogenide compound thin film material according to claim 1, characterized in that: The thickness of the perovskite composite disulfide compound film is 0.3-5.0 μm.

4. The perovskite composite dichalcogenide compound thin film material according to claim 2, characterized in that: The perovskite composite dichalcogenide compound thin film material is an ABX3-WS2 thin film, and the thickness of the ABX3-WS2 thin film is 0.8-2 μm; Or the perovskite composite disulfide compound thin film material is an ABX3-MoS2 thin film, the ABX3-MoS2 thin film has a thickness of 2-3 μm and an average grain size of 170-600 nm.

5. The perovskite composite dichalcogenide compound thin film material according to claim 4, characterized in that: The perovskite composite disulfide compound film material is a BaTiO3-WS2 film, the structure of the BaTiO3-WS2 film is a vertically grown flaky crystal, and the average size of the flaky crystal is 360 nm; Or, the perovskite composite disulfide compound film material is a SrTiO3-WS2 film, the structure of the SrTiO3-WS2 film is short columnar crystals growing vertically, the film surface is granular, and the average size of the granular crystals is 24 nm; Alternatively, the perovskite composite disulfide compound thin film material is a BaSrTiO3-WS2 thin film, and the structure of the BaSrTiO3-WS2 thin film is stacked and grown nanoparticles, and the average size of the nanoparticles is 16 nm.

6. The perovskite composite dichalcogenide compound thin film material according to claim 1, characterized in that: The perovskite composite disulfide compound thin film material is ABX3-MY2, in which the mass ratio of ABX3 to MY2 is (1-50):

100.

7. The method for preparing the perovskite composite disulfide compound thin film material according to any one of claims 1 to 6, characterized in that: The preparation raw materials include perovskite and layered transition metal dichalcogenide; The perovskite is a material with an ABX3 structure, wherein A is one or more +1-valent or +2-valent metals or organic cations; B is one or more +2-valent or +4-valent metals or organic cations; X is one or more -1-valent or -2-valent non-metals or organic anions; The layered transition metal dichalcogenide is a material with a MY2 structure, wherein M is a transition metal of Group IV to VI, and Y is a chalcogen element.

8. The preparation method according to claim 7, characterized in that: The preparation method specifically comprises sputtering a composite target material of perovskite and transition metal disulfide compound onto a substrate surface by radio frequency sputtering to obtain the perovskite composite disulfide compound lubricating film material; Alternatively, the preparation method is specifically to simultaneously sputter a perovskite target material and a layered transition metal disulfide target material on the surface of a substrate by a radio frequency co-sputtering method to obtain the perovskite composite disulfide compound lubricating film material; Among them, the sputtering gas pressure range is 1 ~ 10 Pa; the sputtering bias range is -10 ~ -60 V; the sputtering power is 100 ~ 300 W; the argon gas flow range is 10 ~ 60 sccm; the substrate temperature range is 25 ~ 400 ℃; and the turntable speed range is 1 ~10 rpm.

9. The preparation method according to claim 7, characterized in that: The perovskite is CaTiO3, BaTiO3, SrTiO3, Ba 0.5 Sr 0.5 One of TiO3; And / or, the layered transition metal dichalcogenide is MoS2 or WS2.

10. Use of the perovskite composite disulfide compound film material according to any one of claims 1 to 6 in the field of solid lubrication.